The Buddha Taught Nonviolence, Not Pacifism - Fleischman, Paul R. (Chicago : Pariyatti Publishing, 2002)
In the aftermath of the terrorist attacks of September 11, this thought-provoking essay explores the Buddha's teaching to find one prescription: not war, not pacifism but nonviolence.
Cover; Copyright; Contents; The Buddha Taught Nonviolence, Not Pacifism; Peace Is a State of Mind; References
Description based upon print version of record.
Includes bibliographical references.
Keywords: Religion; Nonviolence -- Religious aspects -- Buddhism; Peace -- Religious aspects -- Buddhism; RELIGION / Buddhism / General; Electronic books